γ-Radiation induces apoptosis via sarcoplasmatic reticulum in guinea pig ileum smooth muscle cells - Claro, Sandra; Oshiro, Maria Etsuko Miyamoto; Freymuller, Edna; Katchburian, Eduardo; Kallas, Esper George; Cerri, Paulo Sérgio [UNESP]; Ferreira, Alice Teixeira (Elsevier, 2008)
We investigated the effects of γ-radiation on cells isolated from the longitudinal smooth muscle layer of the guinea pig ileum, a relatively radioresistant tissue. Single doses (up to 50 Gy) reduced the amount of sarcoplasmatic reticulum and condensed the myofibrils, as shown by electron microscopy 3 days post-irradiation. After that, contractility of smooth muscle strips was reduced. Ca2+ handling was altered after irradiation, as shown in fura-2 loaded cells, with elevated basal intracellular Ca2+, reduced amount of intrareticular Ca2+, and reduced capacitive Ca2+ entry. Radiation also induced apoptosis, judged from flow cytometry of cells loaded with proprium iodide. Electron microscopy showed that radiation caused condensation of chromatin in dense masses around the nuclear envelope, the presence of apoptotic bodies, fragmentation of the nucleus, detachment of cells from their neighbors, and reductions in cell volume. Radiation also caused activation of caspase 12. Apoptosis was reduced by the administration of the caspase inhibitor Z-Val-Ala-Asp-fluoromethyl-ketone methyl ester (Z-VAD-FMK) during the 3 day period after irradiation, and by the chelator of intracellular Ca2+, 1,2-bis(o-aminophenoxy)-ethane-N,N,N′,N′-tetraacetic acid (BAPTA), from 1 h before until 2 h after irradiation. BAPTA also reduced the effects of radiation on contractility, basal intracellular Ca2+, amount of intrareticular Ca2+, capacitative Ca2+ entry, and apoptosis. In conclusion, the effects of gamma radiation on contractility, Ca2+ handling, and apoptosis appear due to a toxic action of intracellular Ca2+. Ca2+-induced damage to the sarcoplasmatic reticulum seems a key event in impaired Ca2+ handling and apoptosis induced by γ-radiation. © 2008 Elsevier B.V. All rights reserved.
Keywords: γ-Radiation; Apoptosis; Calcium; Caspase 12; Ileum; Sarco/endoplasmic reticulum; benzyloxycarbonylvalylalanylaspartyl fluoromethyl ketone; calcium; caspase 12; ethylene glycol 1,2 bis(2 aminophenyl) ether n,n,n',n' tetraacetic acid; fura 2; propidium iodide; animal tissue; apoptosis; calcium cell level; cell nucleus membrane; cell volume; chromatin condensation; electron microscopy; enzyme activation; flow cytometry; gamma radiation; guinea pig; ileum; intestine muscle; muscle fibril; nonhuman; priority journal; radiosensitivity; sarcoplasmic reticulum; smooth muscle contractility; Animals; Caspases; Cells, Cultured; Egtazic Acid; Gamma Rays; Guinea Pigs; Muscle Contraction; Myocytes, Smooth Muscle; Sarcoplasmic Reticulum